Features of sports training of archers based on the use of simulators - Nakonechnyi, Ihor; Sobko, Irina; Gulich, Olena; Borysenko, Natalia; Gulich, Oleg; Gulich, Igor; Vitsko, Sergey; Hryhorenko, Hryhorii (Journal of Physical Education and Sport, 2022)
A qualitative increase in the technical skill of archers requires the use of effective training simulators during sports training. The purpose of the study was to develop and experimentally justify the use of technical devices to increase physical and technical preparation levels of archers. Material and methods. Twenty-six young archers (age 12–13 years old) who participate in archery at City Specialized Children and Youth Sports School of Olympic Archery Reserve "Komunar" in Kharkiv participated in the study. Control and experimental groups of 13 people per group were randomly selected. All participants agreed to participate in the experiment. The study was carried out from January to November 2021. At the beginning of the experiment and at the end of the study, all participants passed physical and technical fitness testing. Testing of athletes in terms of physical readiness (30 m sprint, shuttle run 4x9 meter, forward bend while sitting, long jump from a place, push-ups within 30 seconds, and Romberg’s test), technical readiness (holding the bow in the “stretch”, stretching the bow within 30 s, archery 18 m, archery 60 m) and methods of mathematical statistics were applied. Results. The technical devices “Posture Practice”, “Elbow Pad”, and “Balancing Board” used for the development of physical qualities and technical techniques were previously developed and implemented in the training process of archers. The description and technical characteristics of these training simulators are provided, and the methodology of their application in terms of practical activity of archers was previously described. Conclusions. As a result of the experiment, significant differences were found between the control and experimental groups according to the results of the tests “Shuttle run 4x9 m”,”Stretching the bow by hand in 30 s”, “Archery 18 m”, and “Archery 60 m” (p < 0 .05; p < 0.01) in the experimental group. These indicators were significantly higher in comparison with athletes in the control group. The introduction of training simulators influenced the improvement of the archery technique. The athletes in the experimental group managed to develop a biomechanically appropriate movement structure due to which the indicators of competitive activity increased
Keywords: archery, simulator, technical readiness, physical fitness